Trial on refinement of early stage non-small cell lung cancer: adjuvant chemotherapy with pemetrexed and cisplatin versus vinorelbine and cisplatin: the TREAT protocol ; study protocol - Kreuter, Michael; Vansteenkiste, Johan F.; Griesinger, Frank; Hoffmann, Hans; Dienemann, Hendrik; DeLeyn, Paul; Thomas, Michael (BMC cancer, 2007)
Background: Adjuvant chemotherapy has been proven to be beneficial for patients with early stage non-small cell lung cancer. However, toxicity and insufficient dose delivery have been critical issues with the chemotherapy used. Doublet regimens with pemetrexed, a multi-target folate inhibitor, and platin show clear activity in non-small cell lung cancer and are well tolerated with low toxicity rates and excellent delivery. Methods/Design: In this prospective, multi-center, open label randomized phase II study, patients with pathologically confirmed non-small cell lung cancer, stage IB, IIA, IIB, T3N1 will be randomized after complete tumor resection either to 4 cycles of the standard adjuvant vinorelbine and cisplatin regimen from the published phase III data, or to 4 cycles of pemetrexed 500 mg/m2 d1 and cisplatin 75 mg/m2 d1, q 3 weeks. Primary objective is to compare the clinical feasibility of these cisplatin doublets defined as non-occurrence of grade 4 neutropenia and/or thrombocytopenia > 7 days or bleeding, grade 3/4 febrile neutropenia and/or infection, grade 3/4 non-hematological toxicity, non-acceptance leading to premature withdrawal and no cancer or therapy related death. Secondary parameters are efficacy (time to relapse, overall survival) and drug delivery. Parameters of safety are hematologic and non-hematologic toxicity of both arms ... Trial Registration. Clinicaltrials.gov NCT00349089